2020
DOI: 10.3906/sag-1908-161
|View full text |Cite
|
Sign up to set email alerts
|

Ankaferd hemostat: from molecules to medicine

Abstract: Ankaferd hemostat (ABS; Ankaferd Blood Stopper®, İstanbul, Turkey) is a hemostatic agent having an impact on red blood cell–fibrinogen interactions. The hemostatic effect of ABS depends upon the quick promotion of a protein network, particularly fibrinogen gamma, in relation to the erythrocyte aggregation. The entire physiological process involves ABS-induced formation of the protein network by vital erythrocyte aggregation. Vital erythrocyte aggregation occurs with the spectrine, ankyrin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In recent years many studies were devoted to evaluating the inhibitory activity of many plants on these enzyme families [ 5 , 21 ]. Ankaferd blood stopper ® (ABS) is a hemostatic drug of five different plant origins that has been developed in Anatolia and accepted in the universal literature [ 23 , 28 ]. ABS has been used to stop bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years many studies were devoted to evaluating the inhibitory activity of many plants on these enzyme families [ 5 , 21 ]. Ankaferd blood stopper ® (ABS) is a hemostatic drug of five different plant origins that has been developed in Anatolia and accepted in the universal literature [ 23 , 28 ]. ABS has been used to stop bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Ankaferd blood stopper ® (ABS) is a prominent hemostatic agent that is commonly used in Turkey [ 22 , 23 ]. ABS is a standard mixture of Alpinia officinarum , Gycyrrhiza glabra , Vitis vinifera , Thymus vulgaris , and Urtica dioica [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, alcohol, N-butyl-2-cyanoacrylate, and caustic materials are utilized as tumor embolizers. In colon cancer liver metastases and hepatocellular cancer cases, ABS may be utilized for the palliative, adjuvant, neoadjuvant, or supportive role via interventional radiology methods for the treatment of solid tumors [ 41 ]. In a different study, the antineoplastic role of ABS on the colon cancer cells was identified [ 42 ].…”
Section: Ankaferd Hemostat In Solid Tumorsmentioning
confidence: 99%
“…On the other hand, Ankaferd Blood Stopper (ABS), consisting of Thymus vulgaris (thyme), Glycyrrhiza glabra (liquorice), Vitis vinifera (grape vine), Alpinia officinarum (blue ginger), and Urtica dioica (nettle) plant extracts, has been used as an alternative hemostatic agent in folk medicine for many years [5,6,12]. Recently, it has been widely used in some clinical trials for various tissue injuries as a topical agent for control of minor or major hemorrhages that occur spontaneously, such as gastrointestinal bleeding, or during or following some surgical interventions, including adenoidectomy and tyroidectomy [5,7].…”
Section: Introductionmentioning
confidence: 99%